Improved Routing Protocol for Health Care Communications: A Descriptive Study - K. Murthy, Jayanthi; Rao, V. Sambasiva (Innovations in Science and Technology Vol. 7, 2022)
Wireless Body Area Network (WBAN technology has greatly expanded the possibility of remote healthcare monitoring systems. The devices used for WBAN have limited energy resources, and it is hard to recharge or replace the batteries in most of them. The WBAN data mostly consists of medical information requiring high reliability, security and low delay. The routing protocols play a significant role in transmitting the information. The major goal of this research is to discover the best routing protocol for Wireless Body Area Networks by evaluating the performance of routing protocols using static IEEE 802.15.4. Investigations into different routing protocols point to cluster structure and Ad hoc On Demand Vector (AODV) as the most likely candidate. When improvements were made to consider energy and mobility, a 16 percent improvement in energy usage was discovered, resulting in high residual battery capacity and eliminating the need for recharging the batteries.